An Analysis of Students' Perspective Toward the Classroom Management of English Teaching-Learning Process at MTs NW Putra Rinjani NW - Huddin, M. Zidni; Saputra, Ari; Junaidi, Abdul Majid (Lembaga Yasin AlSys, 2024)
This study has two objectives. The first objective is To describe the Students' Perspective Toward the Classroom Management of English Teaching-Learning Process at MTs NW Putra Rinjani NW .The second objective is To know what the students Problem in learning English Language. The data collection methods used in this study observation and interview. The data analysis method uses a qualitative descriptive method with the stages of data collection, data reduction, data presentation, and drawing conclusions. The result of the study shows that to handle a big class, the teacher uses the conventional seating arrangement. The teacher uses both English and Indonesian in the teaching and learning process in order that the students understand the lesson. To make the students easy to understand the material, the teacher acts as an informer and monitor in the teaching and learning process. The teacher uses small groups in grouping students. The teacher corrects the students’ spoken and written language by checking students’ pronunciation and writing one by one. The teacher gives feedback to the students individually or in groups. The teacher’s voice is loud in explaining the material. It is aimed to make the students hear the teacher’s voice clearly. The teacher’s pronunciation is correct and clear.